Morphometric study of slaughtered Murrah buffalo bull testis and its correlation with seminal attributes of epididymal semen - Kumar, Hridesh; Srivastava, Sushant; Kumar, Rajesh (Buffalo Bulletin, 2022)
Present study was conducted to study the morphometric characteristics of slaughtered Murrah buffalo bull testis and its correlation with seminal attributes of epididymal semen. Total 56 pair of slaughtered Murrah buffalo bull testicles were procured from Allana, slaughterhouse, Arrora, and Mass agro food Pvt. Ltd. Unnao Uttar Pradesh, India; maintained at Deep Frozen Semen Laboratory, College of Veterinary science, and animal Husbadry, Ayodhya, Uttar Pradesh, India. Various morphometric parameters of testes and epididymis were analyzed and their correlations with attributes of epididymal semen were evaluated. No significance difference in seminal attributes between 6 h and 12 h after collection of testicles is clearly indicated that semen can be collect up to 12 h after death of animal without any significance loss in quality of semen in Murrah buffalo bull. Significant strong positive correlation among important characteristics (motility, livability and HOS positive sperm) suggests that these test may be used as one of the test for predicting fertility of epididymal semen Murrah buffalo bull.